О применении r-алгоритма для решения одного класса задач стохастического программирования - Лиховид, А.П. (Теорія оптимальних рішень, 2005)
The paper investigates the efficiency of r-algorithms used to solve stochastic problems with a simple recourse and a random technology matrix of second-stage constraints. The computational results are given for the case, when the SLP-IOR package is used.